Sistemas complejos y modelos multiagentes: Herramientas para el estudio de las dinámicas económicas urbanas (2011)
In recent years, there has been an interesting academic debate about possibilities that complex systems and multi-agent based models provide to study social processes and economic dynamics. The article presents this new theoretical framework and some of its methodological tools through the discussion of two preliminary research: the first explores the existence of networks in the Latin American urban system and the other one refers to a market research of the land at urban peripheries, which emphasizes on the incidence of informality in land use and spatial distribution of prices. The possibility of extending to models and future applications by using this new approach is discussed at the end of the document and it also invites contemporary economic analysts to use such kind of tools.